Developing a Mindfulness Model With the Mediating Role of Self-Compassion in the Marital Adjustment of Women and Men in Tehran - Taghizade Shul, Zohre; Mirhashemi, Malek; Bagheri, Nasrin (KMAN Counseling & Psychology Nexus, 2027)
This study aimed to model the relationships among psychological capital, mindfulness, self-compassion, and marital adjustment in women and men residing in Tehran. The statistical population consisted of married individuals who attended neighborhood community centers in Tehran during 2024–2026. Based on the formula proposed by Tabachnick and Fidell (2005) and considering the number of study components, the required sample size was estimated to be 276 participants, who were selected through multistage random sampling. Data were collected using the Psychological Capital Questionnaire developed by Luthans et al. (2007), the Five Facet Mindfulness Questionnaire (FFMQ), Neff’s Self-Compassion Scale (2003), and Spanier’s Dyadic Adjustment Scale (1976). Path analysis was conducted in AMOS to estimate the direct and indirect effects of the variables. Overall, 44% of the variance in marital adjustment and 71% of the variance in self-compassion were explained by the variables included in the model, whereas approximately 56% of the variance in marital adjustment was attributable to variables outside the model. The results indicated that nonjudging, nonreactivity, and describing had direct effects on marital adjustment. In addition, nonreactivity and nonjudging had significant indirect effects on marital adjustment through the mediating variable of self-compassion. Acting with awareness had no significant effect, whereas describing exerted only a direct effect. Based on the findings, it can be concluded that the marital adjustment of women and men is not merely a secondary phenomenon resulting from positive life experiences, personal characteristics, or similar factors; rather, it should be examined from a comprehensive and interactional perspective.